Analysis of LTE Network Quality of Service on Streaming Application - Putri, RA Rizka Qori Yuliani; Anhar, Anhar; Al Nazen, Aguinaldo; Setiawan, Aris; Kholik, Dede Abdul (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2023)
QoS (Quality of Service) measurement of LTE (Long Term Evolution) networks is carried out using the Telkomsel provider. Measurements were made in Perawang, Riau at night. QoS measurements are carried out at Perawang to evaluate and monitor network quality in accessing vidio streaming services provided by the Telkomsel network in the Perawang, Riau. Measurements were aimed at 5 streaming applications, namely YouTube, RCTI+, Online Radio, Twitch, and Vidio. The reason 5 applications are used for QoS measurement is that these applications are popular applications used in the category of Vidio streaming applications. Measurements were carried out for 160 seconds. The measurement results will be analyzed for quality based on the TIPHON standard. The results were obtained by calculating the data that has been obtained by Wireshark. The data will be calculated using the existing equations. Twitch is the only application that has a value of four in the QoS parameter index category and has a QoS value with an excellent index category. 4 other applications have a QoS value with a good index category. This is due to the low value of the throughput index category. Online Radio and Vidio applications have an index category value of 0. YouTube and RCTI+ applications have a throughput index category value of 1 and 2 respectively. For jitter, packet loss, and delay values, 5 streaming applications have an excellent index category with a value of 4. The measurement results that have been obtained would be displayed in the form of tables and graphs.